The Effect of Environment Literacy in Thematic Learning on Writing Skills and Attitude to Fourth-Grade Elementary School Students - Winarni, Endang Widi; Daimun, Daimun; Purwandari, Endina Putri; Sucipto, Sigit (International Conference on Elementary Education, 2020)
The purpose of this study was to determine the effect Tropical Forest as teaching material on the aspects of poetry writing skills such as the suitability of contents, diction, imagination, mandate, and attitudes of environmental care in fourth-grade for elementary school students. This research used quantitative research methods with The Matching Only Pretest-Posttest Control Group Design. The population was the public elementary school in the Rejang Lebong district. The sample was selected by random cluster sampling, namely elementary school number 93 and elementary school number 119 in Rejang Lebong. The independent variable was the Tropical Forest teaching material, while the dependent variable was poetry writing skills for Indonesian subjects and environmental attitudes of science subjects. The instrument for evaluating poetry writing skills used a rubric with intervals of 1 to 4, while a caring attitude used a questionnaire. The data collection technique was done by filling out an assessment questionnaire from the results of writing poetry individually. Data analysis using IBM SPSS Statistics Version 25, for: (1) validity and reliability, (2) prerequisite tests, and (3) hypothesis testing. The results of the prerequisite test are unnormal for poetry writing skills variable then data were analyzed using the non-parametric Mann-Whitney analysis. While the caring attitude variable shows the normal distribution, then data were analyzed using the parametric t-test. The experiments showed that there was a significant difference in the poetry writing skills for the suitability of contents and the attitudes of environmental care between students who use Tropical Forest as teaching materials and students who use environmental learning resources around the school. Furthermore, there was no significant difference in writing poetry, diction, imagination, and mandate writing skills between students who use Tropical Forest as teaching materials and students who use environmental learning resources